2015
DOI: 10.1590/s0080-623420150000700002
|View full text |Cite
|
Sign up to set email alerts
|

Incidência de úlceras por pressão em pacientes de Unidade de Terapia Intensiva Cardiopneumológica

Abstract: RESUMO Objetivo Identificar e analisar os coeficientes de incidência de úlceras por pressão (UP) e os fatores de risco para o seu desenvolvimento em pacientes críticos com doenças cardiopneumológicas. Método Estudo de coorte, prospectivo realizado na Unidade de Terapia Intensiva (UTI) Cardiopneumológica de um hospital de grande porte na cidade de São Paulo, durante os meses de novembro de 2013 a fevereiro de 2014. Participaram do estudo 370 pacientes maiores de 18 anos, que não apresentavam UP na admissão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
3
56

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 25 publications
6
35
3
56
Order By: Relevance
“…Despite the above, the incidence of this study was higher than that of the study 22 performed in the ICU in the countryside of São Paulo, which de ned the rate as 13.95%; and another study that found an incidence of 11.0% in the city of São Paulo in a cardiopneumological ICU 11 . In addition, the incidence found in this study was also higher than double the average result (10.1%) of the survey, also in São Paulo, with the participation of three teaching hospitals 9 .…”
contrasting
confidence: 82%
See 3 more Smart Citations
“…Despite the above, the incidence of this study was higher than that of the study 22 performed in the ICU in the countryside of São Paulo, which de ned the rate as 13.95%; and another study that found an incidence of 11.0% in the city of São Paulo in a cardiopneumological ICU 11 . In addition, the incidence found in this study was also higher than double the average result (10.1%) of the survey, also in São Paulo, with the participation of three teaching hospitals 9 .…”
contrasting
confidence: 82%
“…However, it should be noted that the study cited did not include ICU in its sample, so it may not be considered a reliable standard of comparison, but it certainly can be interpreted as a north for improvement. Regarding the location of injuries in the sample (Table 4), he highest concentration (76.5%) of PI in the sacral region is an aspect of wide agreement in the literature 8,[10][11][12][13] . In addition to the fact that the second largest portion of PI involvement occurred in the scapular region of the patients, it can be inferred that the skin care of the back, although not exclusive, should be a factor of attention to the health team and, mainly of nursing of the ICU researched.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…There are evidences that intrinsic and extrinsic factors predispose to PI development, so identifying risk factors during patient care is an asset to hospital institutions, which can plan specific intervention measures and put them into practice in order to prevent PI [9]. …”
Section: Introductionmentioning
confidence: 99%